Examining the relation between heart rate variability, flow, and shooting in wheelchair athletes - Kim, Y.; Hwang, S.; Park, S.; Cho, S.; Kim, E. (Exercise Science, 2019)
Among many psychophysiological changes of the human body, analy-sis of heart rate variability (HRV) has gained attention with regard to its relation with athletic performance [1]. HRV ref lects the ability of the heart to respond and change in reaction to unexpected stimuli and envi-ronmental changes, and it evaluates the autonomic nervous system re-sponsible for the regulation of cardiac activity [2]. As certain frequencies of heart rate (HR) are reportedly associated with and inf luence both the sympathetic and parasympathetic branches of the autonomic nervous system, HR is used to evaluate the activation of the systems [3]. HRV is measured in various parameters. In particular, HRV is ana-lyzed in the time domain, which ref lects the RR interval, and in the fre-quency domain, which indicates the activity of the autonomic nervous system. For instance, the standard deviation of RR interval (SDNN) and the root mean square of successive differences (RMSSD), or the square root of the average of the squares of successive differences between adja-cent NNs, are typical time domain parameters. For the frequency do-main, spectrum analysis is used to analyze high frequency (HF, 0.15-0.4 Hz), low frequency (LF, 0.04-0.15 Hz), and very low frequency (VLF, 0.003-0.04 Hz) bands as well as the ratio between LF and HF (LF/HF). An individual`s HRV is analyzed through such measurements to evalu-ate their psychophysiological changes. The time domain method in-volves the mathematical calculation of changes in RR intervals, or the ORIGINAL ARTICLE PURPOSE: Heart rate variability leads affective changes, which are associated with athletic performance. This study aimed to examine the relationship between heart rate variability, athletic flow, and shooting performance in wheelchair shooting athletes. METHODS: Eight male and female wheelchair shooting athletes were participated in the study. Heart rate variability was measured at rest and during shooting practice and competitions. Flow experience and shooting score were collected only during practice and actual shooting. SPSS Windows 25.0 was used to perform the following analysis. A repeated one-way ANOVA was applied to analyze the dif-ferences in heart rate variability at rest, during practice and actual shooting. In order to see the linear and curvilinear relationship among the variables, a hierarchical regression analysis was conducted. RESULTS: The level of average heart rate and the ratio of Low Frequency (LF) to High Frequency (HF) of heart rate variability were significantly at different situations. At the resting period average heart rate was the highest while LF/HF was the lowest, which indicated that LF was less activated than HF at rest as compared to actual shooting. A hierarchical regression analysis showed that flow was a sig-nificant linear predictor for shooting performance. CONCLUSIONS: Heart rate variability is changing depending on the circumstance that athletes faced to, which suggests that the changes may be associated with psychological states and performance.